Factors Influencing Indonesian Students Satisfaction During their Studies in China - Sandy, William (Asian Journal of Contemporary Education, 2018)
Since more Indonesian students are coming to pursue higher education in China, understanding the factors influencing Indonesian students’ satisfaction could facilitate Chinese higher education institutions and the policymakers to improve and develop their services to match the needs of current Indonesian students in China and to attract potential Indonesian students to study in Chinese higher education institutions. Therefore, the main objectives of this study were (1) to analyze influential factors on Indonesian students’ satisfaction toward Chinese higher education, (2) to examine level of Indonesian students’ satisfaction toward Chinese higher education, and (3) to provide recommendations for both Chinese higher education institutions and the related policymakers. This study applied quantitative approach by using questionnaire as a tool to collect primary data from the 215 Indonesian students currently studying in several universities in Wuhan. The findings indicated four factors have significant positive influence on Indonesian students’ satisfaction toward Chinese higher education. These four factors are education service, infrastructure and staff support, safety, and students’ preparation before coming to China. The multiple regression models with these four factors could predict 60.8% of the variance in the overall Indonesian students’ satisfaction.